'Wasters, agnostics, enforcers, competitors, and community integrators': Reclaimers, S@S, and the five types of residents in Johannesburg, South Africa. (February 2022) - Samson, Melanie; Kadyamadare, Grace; Ndlovu, Lufuno; Kalina, Marc
Highlights: In Johannesburg, reclaimers have not been integrated into separation at source (S@S) Un-integrated S@S forces residents to make a political choice to include reclaimers. Residents as: wasters, agnostics, enforcers, community integrators, and competitors. Without integration, S@S acts as a disintegration project for reclaimers. Abstract: Within South Africa's recycling economy, informal waste pickers (also known as reclaimers) generate immense value for local waste management systems by diverting waste from landfills. However, official municipal separation at source (S@S) programmes, that task residents with sorting recyclables from their waste for separate collection, have failed to integrate reclaimers' unofficial collection system. This dislocates reclaimers, forcing them to work on the margins of municipal S@S programmes and forge separate links with residents to maintain access to recyclables. Drawing on extensive qualitative research in Johannesburg, South Africa, this article reflects on how residents in three different residential neighbourhoods understood and interacted with reclaimers' unofficial collection system and the official S@S programme run by the city. Our findings suggest that five types of residents emerge: wasters (who did not see the value in recycling), agnostics (who did not care who collected their recyclables), enforcers (who actively prevented reclaimers from accessing recyclables), community integrators (who gave their materials to reclaimers); and competitors (who supplemented their own income by selling recyclables). We argue that residents and reclaimers play active roles in shaping official S@S on the ground, and cannot be ignored when developing S@S programmes. Furthermore, S@S and integration are inherently related, as they each target the same residents and the same recyclables, and therefore cannot be understood or addressed in isolation. Unless a specific commitment is made to integrate S@S, S@S becomes a reclaimer dis-integration programme. These findings have broad implications for how S@S should be conceptualised, designed, and implemented.